Survey on the satisfaction of municipal services / Zaherawati Zakaria - Zakaria, Zaherawati (Universiti Teknologi MARA, Kedah, 2016)
In Malaysia, there has been growing media attention and discussion on cases of poor service quality given by public sector including local government agencies. The agencies involved have been pushed to improve the quality of public service delivery. Realizing that some actions has taken place in responding to the public complaint, thus, this study tries to determine to what extent residents of Majlis Perbandaran Sungai Petani (MPSPK) satisfy with municipal services, such as, waste management, cleanliness, culverts and drainage in Sungai Petani. The findings in this study are derived from quantitative method and shows that households has a positive association with municipal services offered by the council. The results prove that the respondents were proud to be a Sungai Petani’s citizen. The findings also indicated that, overall, the households were satisfied with services offered even though got some department that create dissatisfaction to them. For the policy recommendations, the genuine service improvement is sought. In future research, the engagement between all parties should be concerned on local government, private and voluntary sectors, service providers and private citizens in enhancing the levels of customer’s satisfaction.